Crisis Management in South East Asia’s Tourism Industry: Resilience and Adaptation Strategies - Tuli, Ferdouse Ara; Vadiyala, Vishal Reddy (Global Disclosure of Economics and Business, 2022)
Crisis management in Southeast Asia’s tourism industry is imperative due to the region’s vulnerability to various crises, including natural disasters, health emergencies, political unrest, and economic downturns. This study investigates resilience and adaptation strategies employed by stakeholders to mitigate the impacts of crises and promote sustainable tourism development. The study’s objectives include analyzing crisis types, stakeholder roles, and the effectiveness of strategies. Employing a secondary data-based review approach, the study synthesizes existing literature to identify critical insights. Significant findings highlight the importance of collaboration, innovation, sustainability, and adaptability in crisis management. Policy implications emphasize the need for proactive planning, stakeholder engagement, sustainable practices, and capacity building. The study underscores the importance of addressing limitations and contextual factors to enhance the resilience and adaptive capacity of Southeast Asia’s tourism industry in navigating crises and promoting long-term sustainability.